Unusual, selective, reductive, deoxygenation of cyclopentenone alcohols - Bavikar, Suhas R.; Lasonkar, Trupti P.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2014)
A selective, reductive, deoxygenation of 2-aryl-4-hydroxycyclopent-2-en-1-ones to afford 2-aryl-cyclopent-2-en-1-ones was achieved by NaBH4-CeCl3 in methanol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cyclopentenone alcohol; Enone; Luche reduction; Reductive deoxygenation